2018
DOI: 10.1139/gen-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the AP2/ERF transcription factor family in pepper (Capsicum annuumL.)

Abstract: The AP2/ERF family is one of the largest transcription factor families in the plant kingdom. AP2/ERF genes contributing to various processes including plant growth, development, and response to various stresses have been identified. In this study, 175 putative AP2/ERF genes were identified in the latest pepper genome database and classified into AP2, RAV, ERF, and Soloist subfamilies. Their chromosomal localization, gene structure, conserved motif, cis-acting elements within the promoter region, and subcellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 75 publications
6
47
0
Order By: Relevance
“…The classification of the tree was defined and annotated based on the proposed by Nakano et al [15], and it ultimately defined 11 groups. This result was similar to that of Jin's study in peppers [50], no matter the topology or classification of the tree. However, in this study, both groups X and IX were subdivided, and a new group XI was identified.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The classification of the tree was defined and annotated based on the proposed by Nakano et al [15], and it ultimately defined 11 groups. This result was similar to that of Jin's study in peppers [50], no matter the topology or classification of the tree. However, in this study, both groups X and IX were subdivided, and a new group XI was identified.…”
Section: Discussionsupporting
confidence: 90%
“…Although the AP2/ERF superfamily in peppers was reported by Jin et al [50], they indicated that CaAP2/ERFs might be involved in the response to P. capsici in peppers. Capsorubin and capsaicinoids are unique to Capsicum spp., and they possess high economic and nutritional values.…”
Section: Discussionmentioning
confidence: 90%
“…The classi cation of the tree was de ned and annotated based on the proposed by Nakano et al [15], and it ultimately de ned 11 groups. This result was similar to that of Jin's study in peppers [50], no matter the topology or classi cation of the tree. However, in this study, both groups X and IX were subdivided, and a new group XI was identi ed.…”
Section: Discussionsupporting
confidence: 90%
“…The AP2/ERF superfamily is one of the largest TF families in the plant kingdom, and it has been successfully identi ed and investigated in many plant species of sequenced genomes [47][48][49]. Although the AP2/ERF superfamily in peppers was reported by Jin et al [50], they indicated that CaAP2/ERFs might be involved in the response to P. capsici in peppers. Capsorubin and capsaicinoids are unique to Capsicum spp., and they possess high economic and nutritional values.…”
Section: Discussionmentioning
confidence: 99%
“…The genome wide analyses of each transcription factor have been completed and "-"indicates the genome wide analysis was not done yet. Potato's WRKY [63] Dof [58], NAC [145]; ARF [192]; ERF [181] Pepper WRKY [193] ERF [194]; Dof [51] MYB [103]; ARF [190]; NAC [195] Tomato WRKY [62] Dof [53] MYB [88] HSF [120] ARF [196] ERF [171]; Eggplant's WRKY [197] Dof [52] MYB [84].…”
Section: List Of Major Transcription Factors In Major Solanaceous Foomentioning
confidence: 99%